Pengembangan Laboratorium Virtual Bermuatan Project-Based Learning Berbasis Android Untuk Meningkatkan Pemahaman Siswa SMK Pada Mata Pelajaran Komputer Dan Jaringan Dasar - Pratama, Muchammad Ryan; Elmunsyah, Hakkun; Asfani, Khoirudin; Aprillia, Dewi (Jurnal Transformatika, 2023)
The Covid-19 outbreak has changed the learning system in Indonesia from face to face to distance. This causes the practicum learning process to experience difficulties because the practicum requires a real laboratory so that practicum activities can be carried out. Therefore, to solve these problems through the development of virtual laboratory learning media containing Android-based PjBL to improve student understanding. The existence of a virtual laboratory allows students to carry out practical simulations through these learning media flexibly. The development method used is Successive Approximation Model 1 with 3 iterative stages, namely (1) Evaluate, (2) Design, and (3) Develop. The test results of user testing get a percentage value of 88.17% with a very valid category. It was concluded that the learning media developed was very feasible to use and quite effective in increasing the understanding of SMK students majoring in TKJ on Computer and Basic Network subjects.